2018
DOI: 10.3389/fphar.2018.01443
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Properties of DNA Hypomethylating Agents: Selecting the Optimal Epigenetic Partner for Cancer Immunotherapy

Abstract: DNA hypomethylating agents (DHAs) play a well-acknowledged role in potentiating the immunogenicity and the immune recognition of neoplastic cells. This immunomodulatory activity of DHAs is linked to their ability to induce or to up-regulate on neoplastic cells the expression of a variety of immune molecules that play a crucial role in host-tumor immune interactions. To further investigate the clinical potential of diverse epigenetic compounds when combined with immunotherapeutic strategies, we have now compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 35 publications
2
19
0
Order By: Relevance
“…Although the relative contributions of guadecitabine and ipilimumab to this finding cannot be unequivocally dissected, CTLA-4 blockade probably plays an active role due to its effect on T-cell function. On the other hand, upregulation of HLA class I molecules observed on melanoma cells in the majority of investigated tumor samples corroborates their established upregulation previously reported in vitro (28) and in syngeneic mouse models (18) with various DHAs, including guadecitabine (8,19).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Although the relative contributions of guadecitabine and ipilimumab to this finding cannot be unequivocally dissected, CTLA-4 blockade probably plays an active role due to its effect on T-cell function. On the other hand, upregulation of HLA class I molecules observed on melanoma cells in the majority of investigated tumor samples corroborates their established upregulation previously reported in vitro (28) and in syngeneic mouse models (18) with various DHAs, including guadecitabine (8,19).…”
Section: Discussionsupporting
confidence: 89%
“…These phenotypic changes induced or upregulated antigen-specific T-cell recognition of neoplastic cells (3)(4)(5). More recently, DHAs have also been shown to contribute to the activation of cellular immunity by modulating T helper 1-type (Th1) chemokines (6) and IFN-related genes (7,8). In addition, the DHA decitabine was also found to enhance CD8 þ T-cell activation and proliferation, and to improve the cytolytic activity of human IFN gamma þ T cells, which correlated with improved antitumor responses and survival of patients with solid tumors (9).…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, many clinical trials, which include AZA or DAC therapy, combine the therapy with CTLA-4 or PD-L1/2 inhibitors, in order to improve the outcome of the treatment [119][120][121]. Apart from AZA and DAC, another DHA-guadecitabineincreases the level of Ctla4 in melanoma and hematological cancer cells [122]. MTX also increases Ctla4 expression indirectly via its action on the Foxp3 methylation level and DNMT1 reduction.…”
Section: Ctla4 Modifications Through Changes In Dna Methylationmentioning
confidence: 99%
“…In a phase I dose-escalation experiment of 5-AZA-CdR in 12 patients with recurrent epithelial ovarian cancer, Odunsi et al observed increased T cell responses in most patients 111. The mRNA expression of testicular cancer antigens involved in NK and T cell signalling and recruitment, immune checkpoint blocking molecules, immunostimulatory cytokines, and genes involved in the interferon pathway was higher after treatment with guadecitabine(SGI-110) and DAC compared with the immunomodulatory effects of AZA treatment 112. In addition, this combination reduced the number of MDSCs, indicating that the immunomodulatory effects of DNMTi may be useful for immunotherapy 113.…”
Section: Dnmti: Contributor To Cancer Immunotherapymentioning
confidence: 99%